Workplace communication technology focusing on implementing accurate language in emails - Nazifah Hamidun,; Nor Suhaila Che Pa,; Mohd Syamril Aklmar Chek Kassim,; Mohd Hasri Ahmad Shukeri, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Information and communication technology has evolved rapidly which allows the users to share the information online smoothly. The speed of sending the information via technology is extraordinary and offers loads of benefits to the users. There are many types of communication that can be opted by the users. Email is one of the essential communication medium that can be used to convey the message and information. It works speedily in transmitting the message and information to the users in a formal setting or to the workers especially in the organization. In using email, language plays the main role in order to ensure the recipients comprehend the message clearly. Hence, the users need to use the proper language in order to enhance the communication with others successfully. Nevertheless, the language utilized in the email sometimes is not employed precisely which can cause the users confused and unable to comprehend the message easily. The sender neglects to use the accurate language in the email as they concern more on the message to the target recipients. If this scenario keeps on continuing without any solution, it will give the negative impact to the other email users. Hence, the main aim of this study is to discover the effect of using the accurate language in email. This study focuses on two aspects of language; lexical and morphology. The methodology employed in this study was qualitative method. The researchers had carried out the content analysis by interpreting and analyzing the data thoroughly.